1995
DOI: 10.1007/bf02197281
|View full text |Cite
|
Sign up to set email alerts
|

Physical similarity and the equal-environment assumption in twin studies of psychiatric disorders

Abstract: The equal-environment assumption (EEA), upon which twin methodology is based, was examined for the impact of physical similarity on phenotypic resemblance in five common psychiatric disorders: major depression, generalized anxiety disorder, phobia, alcoholism, and bulimia. A population-based sample of 882 female-female twin pairs of known zygosity was rated for similarity of appearance by color photographs. Psychiatric diagnoses were made by clinical assessment of personal interviews of the twins. Structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 28 publications
6
112
2
Order By: Relevance
“…inappropriately inflating estimates of trait heritability). Such characteristics, for example, physical twin similarity (Hettema et al 1995), self-perceived zygosity (Xian et al 2000), perceived zygosity and associated parental approach to rearing their twins (Kendler et al 1993(Kendler et al , 1994Kendler & Gardner, 1998 ;Cronk et al 2002), and physical and emotional closeness between the twins (LaBuda et al 1997 ;Kendler & Gardner, 1998;Cronk et al 2002) have been shown to be uncorrelated with zygosity differences in a number of psychiatric disorders such as alcohol and illicit drug dependence, major depression, anxiety, and externalizing disorders, supporting the validity of the equal environmental assumption in twin studies assessing these disorders. The equal environment assumption has also been found to be valid for DSM-III-R nicotine dependence in female (Kendler & Gardner, 1998) and male twins (Xian et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…inappropriately inflating estimates of trait heritability). Such characteristics, for example, physical twin similarity (Hettema et al 1995), self-perceived zygosity (Xian et al 2000), perceived zygosity and associated parental approach to rearing their twins (Kendler et al 1993(Kendler et al , 1994Kendler & Gardner, 1998 ;Cronk et al 2002), and physical and emotional closeness between the twins (LaBuda et al 1997 ;Kendler & Gardner, 1998;Cronk et al 2002) have been shown to be uncorrelated with zygosity differences in a number of psychiatric disorders such as alcohol and illicit drug dependence, major depression, anxiety, and externalizing disorders, supporting the validity of the equal environmental assumption in twin studies assessing these disorders. The equal environment assumption has also been found to be valid for DSM-III-R nicotine dependence in female (Kendler & Gardner, 1998) and male twins (Xian et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…If this so-called equal environment assumption is violated, the estimates of genetic influence could be falsely inflated. However, this assumption has recently been examined for several psychiatric disorders and found to be quite tenable (52,53). Second, it is important to acknowledge that the method we used to identify the twin sample was not ideal.…”
Section: Discussionmentioning
confidence: 99%
“…Violations of this "equal environments assumption" (EEA) imply that estimated heritabilities overestimate true heritabilities. 5 The EEA provides the most principled grounds for radical doubt regarding twin studies, but various means of indirect assessment-for example, by studying DZ twins mistakenly believed by their families to be MZ-provide no empirical grounds to think violation of the assumption is commonly anywhere near enough to nullify findings of substantial heritability (e.g., Kendler et al 1993;Hettema, Neale, and Kendler 1995;Bradshaw 2007). Designs not involving twins have also not revealed radically divergent findings (Plomin et al 2001).…”
Section: Genes As Causes Of Individual Outcomesmentioning
confidence: 99%